2003
DOI: 10.1136/bjo.87.6.704
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic aspects in patients with central serous chorioretinopathy

Abstract: Aims: Patients with central serous chorioretinopathy were tested for psychosomatic symptoms and social support at the onset of their ailments; their personality profiles were also tested. Methods: 24 consecutive outpatients at the department of ophthalmology, Freiburg University Hospital, Freiburg, Germany, presenting with central serous chorioretinopathy filled in the following standardised questionnaires: Symptom Checklist 90-R (SCL 90-R), Symptom List, Questionnaire on Social Support, and Sixteen Personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 13 publications
3
57
1
4
Order By: Relevance
“…It is a 90-item multidimensional questionnaire used to screen for a broad range of psychological problems. Each of the 90 items is rated on a five-point Likert scale of distress, ranging from ''not at all'' (0) to ''extremely'' (4). Subsequently, the answers are combined in the 10 primary symptom dimensions: somatization, obsessive-compulsiveness, interpersonal sensitivity, depression, anxiety, angerhostility, phobic anxiety, paranoid ideation, psychotism, and others.…”
Section: Symptom Check List-90 Revised (Scl-90-r)mentioning
confidence: 99%
“…It is a 90-item multidimensional questionnaire used to screen for a broad range of psychological problems. Each of the 90 items is rated on a five-point Likert scale of distress, ranging from ''not at all'' (0) to ''extremely'' (4). Subsequently, the answers are combined in the 10 primary symptom dimensions: somatization, obsessive-compulsiveness, interpersonal sensitivity, depression, anxiety, angerhostility, phobic anxiety, paranoid ideation, psychotism, and others.…”
Section: Symptom Check List-90 Revised (Scl-90-r)mentioning
confidence: 99%
“…People referred to as having a type A personality are usually characterized by a highly status-conscious, ambitious and rigidly organized pattern of behavior [57]. Further risk factors that have been proposed include pregnancy, alcohol consumption, untreated hypertension, use of antibiotics, bone marrow or organ transplantation, infection of the respiratory tract and infection with Helicobacter pylori [12,44,58,59,60,61,62,63]. …”
Section: Systemic and Ocular Risk Factorsmentioning
confidence: 99%
“…Wang et al [1] , Spahn et al [14] and Conrad et al [15] noted that patients with poor coping mechanisms when exposed to a stressful situation like divorce, critical illness developed CSCR. Gelber et al [17] found that acute stressors preceded the onset of CSCR by a week.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] CSCR has been associated with severe psychosocial stressors. [14,15] Thomas Holmes and Richard Rahe in 1967 designed Social Readjustment Rating Score based on 43 life events to study if stress contributes to an illness. [16] Rather than taking an unstructured history they thought it is better to have a list of commonly involved stressors which ranged from death of spouse to change in sleep pattern.…”
Section: Introductionmentioning
confidence: 99%